Historical Considerations and Innovations in the Perioperative Use of Mitomycin C for Glaucoma Filtration Surgery and Bleb Revisions. Issue 3 (March 2020) - Grover, Davinder S.; Kornmann, Helen L.; Fellman, Ronald L.
Abstract : Although there is a currently a revolution in angle-based procedures, subconjunctival filtration surgery with mitomycin C (MMC) wound modification remains a vital skill for glaucoma surgeons. MMC is a potent antifibrotic agent that has been an invaluable adjunct for successful glaucoma filtration surgery for over 20 years, but it must be used judiciously to avoid serious complications, including hypotony, corneal decompensation, bleb avascularity, bleb leaks, blebitis, and endophthalmitis. The purpose of this report is to describe the historical lessons learned from MMC use, along with updated methods of MMC delivery during primary trabeculectomy, bleb needling at the slit lamp, bleb revisions in the operating room, and newer and less invasive ab-interno filtering procedures. Information for the review was gathered using an extensive search on PubMed, a review of all available peer-reviewed literature, and the authors' personal clinical judgment and experience.